Molecular Patterns of Subclinical and Clinical Rejection of Kidney Allograft: Quantity Matters - Mariana Wohlfahrtova; Irena Tycova; Eva Honsova; Alena Lodererova; Ondrej Viklicky (Karger Publishers, 2015)
Background/Aims: Subclinical rejection diagnosed from protocol biopsies is thought to be a risk factor of long- term allograft dysfunction. The reason why in some patients subclinical rejection does not represent risk for progression is not fully understood. Methods: The intragraft expression of 376 target genes involved in chemokine defense, apoptosis, inflammation, tolerance and TGF-β signalling pathways was measured using quantitative real-time RT-PCR (2-∆∆Ct) method in subclinical inflammation (SCI, n=10), clinical inflammation in acute T-cell mediated rejection (CI, n=10) and no rejection samples (n=9). Results: Clinical inflammation group showed a increased expression of genes for chemotaxis mediating cytokines (CCL1, CCL17, CCL24, CCL25, CCL26), cytokine receptors (CCR1, CCRL2, IL1RAPL2, CXCR5), proinflammatory cytokines (IL12A, LTA), inflammatory mediator (PTAFR), complement protein C3, executioner protein of apoptosis (CASP7), growth factor (TGFA), colony stimulating factor (CSF-2), proteins involved in dendritic cells differentiation and interaction (CD209, LAMP3), regulation of immune response (LILRB2, LILBRB4). The quantitative difference in transcripts signature between SCI and CI is consistent with stronger proinflammatory setting of CI. Prostaglandin E2 receptor gene expression was independently associated with lower risk of further graft function deterioration (OR 0.11, CI 0.01-0.78, pConclusion: Subclinical acute kidney inflammation has transcriptional profile of immune injury of lower extend compared to clinical acute inflammation.